ANGKA KEJADIAN OBESITAS SENTRAL PADA MASYARAKAT KOTA PEKANBARU - Sundari, Elsa; Masdar, Huriatul; Rosdiana, Dani (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Obesity has become a big problem in the world mostly known asglobesity. Central obesity can cause degenerative diseases such ascardiovascular diseases, diabetes mellitus and cancer. This research informed theincidence of central obesity in Pekanbaru community. Descriptive cross sectionalstudy method was used in this research and two hundred sixty people were involved.Determination of central obesity in this research used waist circumferencemethode. In which waist circumference ≥ 90 cm in men and ≥ 80 in woman werecategorized as central obesity . The result shows 165 people with central obesity(63,4%). The insidence of central obesity in Pekanbaru community was higher inwoman (55%), age > 60 years old (79,1%), high education (65,9%) and housewife(77,3%).Key word : Obesity, Central obesity, Pekanbaru city.